Tracing Students’ Cognitive Progression in Geometry: A Design-Based Research Through the Van Hiele Model of Instruction and Ethnomathematics - Ipah Muzdalipah; Marsigit Marsigit; Sri Andayani (Universitas Pendidikan Mandalika, 2026)
This study investigated students’ cognitive progression in geometry based on Van Hiele levels. It used a design-based research approach that integrates the Van Hiele Model of Instruction with ethnomathematics, following the McKenney & Reeves design cycle (analysis and exploration, design and construction, and evaluation and reflection). Data were collected through Van Hiele tests, observations, teachers and students interview, and documentation, and analysed using qualitative methods (data reduction, data display, and conclusion drawing/verification). The pilot class (cycle 1) was conducted with 34 eighth-grade students at SMPN 6 Tasikmalaya in August 2025, while actual class (cycle 2) was carried out with 33 eighth-grade students at SMPN 13 Tasikmalaya in September 2025. The research results showed that students’ cognitive development peaked at the visualization phase in both the pilot class (85%) and the actual class (94%), with fewer students progressing to higher levels. However, the actual class (61% at the formal deduction level) demonstrated notable improvement compared to the pilot class (41% at the formal deduction level), due to refinements in instructional design. These findings suggest that integrating ethnomathematics with the Van Hiele model effectively enhances students’ geometric thinking.